2020
DOI: 10.48550/arxiv.2009.11450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray constraints on the spectral energy distribution of the $z=5.18$ blazar SDSS J013127.34-032100.1

Hongjun An,
Roger W. Romani

Abstract: We report on X-ray measurements constraining the spectral energy distribution (SED) of the highredshift z = 5.18 blazar SDSS J013127.34−032100.1 with new XMM-Newton and NuSTAR exposures. The blazar's X-ray spectrum is well fit by a power law with Γ = 1.9 and N H = 1.1 × 10 21 cm −2 , or a broken power law with Γ l = 0.5, Γ h = 1.8, and a break energy E b = 0.7 keV for an expected absorbing column density of N H = 3.6 × 10 20 cm −2 , supported by spectral fitting of a nearby bright source. No additional spectra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The observed 0.5 − 2 keV flux of J074749+115352 is F 0.5−2keV = 3.49 +0.44 −0.45 × 10 −14 erg s −1 cm −2 . To our knowledge, this is the X-ray brightest radio quiet quasar at z > 5, only after two radio loud blazars [Q0906+6930 at z = 5.48, Romani (2006); SDSS J013127.34-032100.1 at z = 5.18, An & Romani (2020)] and a radio loud non-blazar quasar CFHQS J142952+544717 at z = 6.18 recently detected in X-ray by Medvedev et al (2020) with eROSITA (the X-ray brightest quasar at z > 5, with an observed 0.3 − 2 keV Å is the monochromatic luminosity at 2500 Å, and is computed from M 1450 assuming a power law spectral index of α = −0.5 in UV band. N H is the Galactic foreground absorption column density toward the quasar obtained from the HEASARC webtools using the HI4PI full-sky H I map (HI4PI Collaboration 2016).…”
Section: Observations and Data Analysismentioning
confidence: 93%
“…The observed 0.5 − 2 keV flux of J074749+115352 is F 0.5−2keV = 3.49 +0.44 −0.45 × 10 −14 erg s −1 cm −2 . To our knowledge, this is the X-ray brightest radio quiet quasar at z > 5, only after two radio loud blazars [Q0906+6930 at z = 5.48, Romani (2006); SDSS J013127.34-032100.1 at z = 5.18, An & Romani (2020)] and a radio loud non-blazar quasar CFHQS J142952+544717 at z = 6.18 recently detected in X-ray by Medvedev et al (2020) with eROSITA (the X-ray brightest quasar at z > 5, with an observed 0.3 − 2 keV Å is the monochromatic luminosity at 2500 Å, and is computed from M 1450 assuming a power law spectral index of α = −0.5 in UV band. N H is the Galactic foreground absorption column density toward the quasar obtained from the HEASARC webtools using the HI4PI full-sky H I map (HI4PI Collaboration 2016).…”
Section: Observations and Data Analysismentioning
confidence: 93%